2012
DOI: 10.1089/scd.2011.0674
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Paracrine Factor Expression in Human Adult Mesenchymal Stem Cells Derived from Bone Marrow, Adipose, and Dermal Tissue

Abstract: Human adult mesenchymal stem cells (MSCs) support the engineering of functional tissue constructs by secreting angiogenic and cytoprotective factors, which act in a paracrine fashion to influence cell survival and vascularization. MSCs have been isolated from many different tissue sources, but little is known about how paracrine factor secretion varies between different MSC populations. We evaluated paracrine factor expression patterns in MSCs isolated from adipose tissue (ASCs), bone marrow (BMSCs), and derma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
297
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 362 publications
(312 citation statements)
references
References 73 publications
10
297
0
5
Order By: Relevance
“…To investigate the proangiogenic paracrine capacity of W8B2 1 CRSCs, a Matrigel endothelial network assay was used [17]. In comparison with the control group, HCMEC cultured in conditioned medium harvested from W8B2 1 CRSCs showed a significant improvement in tubular network formation on Matrigel in term of number of complete ring formed and branching points but not the average length of network formed.…”
Section: Conditioned Medium Derived From W8b2 1 Crscs Promotes Angiogmentioning
confidence: 99%
“…To investigate the proangiogenic paracrine capacity of W8B2 1 CRSCs, a Matrigel endothelial network assay was used [17]. In comparison with the control group, HCMEC cultured in conditioned medium harvested from W8B2 1 CRSCs showed a significant improvement in tubular network formation on Matrigel in term of number of complete ring formed and branching points but not the average length of network formed.…”
Section: Conditioned Medium Derived From W8b2 1 Crscs Promotes Angiogmentioning
confidence: 99%
“…MSCs also secrete various cytokines and angiogenic mediators that repair damaged tissues (10). A previous comparative study has indicated that the umbilical cord (UC) is an excellent alternative to bone marrow (BM) as a source of MSCs for cell therapy (11).…”
Section: Introductionmentioning
confidence: 99%
“…AT is composed of adipocytes and various cell types among which are a population of multipotent progenitors, termed adipose stromal cells (ASCs) [4]. ASCs display similar but not identical features with their bone marrow (BM) counterparts, mesenchymal stromal cells (MSCs) [5][6][7][8][9]. Like MSCs, ASCs are endowed with multilineage mesodermal differentiation potentials and exhibit extensive paracrine and immune-modulatory properties [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%